2009
DOI: 10.1590/s0124-00642009000500002
|View full text |Cite
|
Sign up to set email alerts
|

Costo efectividad de la vacunación contra influenza en menores de 2 años y mayores de 65 años en Colombia

Abstract: This study's results supported the Colombian Ministry of Health's initiative for introducing yearly flu vaccination amongst small children and older adults in Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…In the second scenario, we took values for GP consultation, hospitalization and mortality rates from 2 Colombian studies, 45,46 which were extrapolated to the age groups of analysis using US data from Molinari et al 38 …”
Section: Data Inputsmentioning
confidence: 99%
“…In the second scenario, we took values for GP consultation, hospitalization and mortality rates from 2 Colombian studies, 45,46 which were extrapolated to the age groups of analysis using US data from Molinari et al 38 …”
Section: Data Inputsmentioning
confidence: 99%
“…In 2007, a Colombian economic study estimated in 230 and 2500 the annual number of deaths among children <2 years and adults >65 years, respectively. 17 On average, >30 000 cases in both age groups would require in-hospital care every year. Another analysis found that general mortality increase between 2% and 11% when influenza virus circulated in Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Over 65 years: In 23 of 25 studies, vaccination was considered cost-effective [ 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 ]. The studies were carried out with economic models in 20 countries (including eight countries in the Americas) and analyzed vaccination with trivalent vaccine, or CE of the use of high-dose trivalent, with adjuvants, or quadrivalent.…”
Section: Resultsmentioning
confidence: 99%